Application of Lean Manufacturing Methods to Streamline the Welding Line - Bucko, Michal; Schindlerova, Vladimira; Sajdlerova, Ivana (Manufacturing Technology Journal, 2020)
This paper deals with the use of lean manufacturing methods to streamline the welding line in the au-tomotive industry. The automotive industry is constantly developing and innovating its production envi-ronments and technology because of growing competition on the market and customer demands. Cur-rent trends of car makers include pressure to reduce costs and increase production efficiency. With the commencement of new technologies, the production lines began to innovate and the production cycle began to constantly accelerate. The paper deals with the reconstruction of the welding line, which produces parts for the rear axle of a compact SUV. The case study aims to identify bottlenecks and set innovation plans and their evaluation in possible implementation. In the paper, lean manufacturing methods are applied in order to deter-mine the ideal solution for ensuring the quality and ensuring the efficiency of the production line, lead-ing to cost reduction. Through these innovations and modernizations, the company will be heading for digitalisation that changes the core of the industry.
Keywords: Lean Manufacturing; Optimization; Automotive; Production Line; Welding